Graphene oxide and graphene nanosheet reinforced aluminium matrix composites: Powder synthesis and prepared composite characteristics. (15th March 2016) - Liu, Jinghang; Khan, Umar; Coleman, Jonathan; Fernandez, Bea; Rodriguez, Pablo; Naher, Sumsun; Brabazon, Dermot
Abstract: The preparation and properties of reduced graphene oxide (rGO) and graphene nanosheets (GNSs) reinforcement of aluminium matrix nanocomposites (AMCs) are reported. For the rGO-AMCs, commercial colloidal GO was coated onto aluminium powder particles and then reduced via thermal annealing. For the GNS-AMCs, graphene exfoliated from graphite through ultrasonication and centrifugation was coated onto aluminium particle surfaces via dispersion mixing, filtering and drying. Pure aluminium and aluminium composites with various reinforcement concentrations of rGO and GNS were cold compacted into disc-shaped specimens and sintered in inert atmosphere. The mechanical properties and microstructure were studied and characterised via Vickers hardness, X-ray diffraction, density measurement, and scanning electron microscopy. The reinforcements were uniformly distributed onto the aluminium particle surfaces before and after consolidation within the composites. The relevant factors for the powder metallurgy process (compaction pressure, density, and sintering conditions) were optimised. Increased levels of increased hardness were recorded, over baseline compacted and sintered pure aluminium samples, prepared under identical experimental conditions, of 32% and 43% respectively for the 0.3 wt.% rGO-Al and 0.15 wt.% GNSs-Al composites. The process developed and presented herein provides encouraging results for realising rGO-AMC and GNS–AMC nanocomposites via low cost cold powder compaction and sintering metallurgy techniques. Graphical abstract: Highlights: Developed powder metallurgy method for rGO and GNS-aluminium matrix composites Mechanical and chemical property determination of for graphene–aluminium composites Significant increase in composite compact hardness over pure metal baseline Correlation of composite density with compaction pressure and reinforcement levels Elaboration of areas of focus on method for further improvements in graphene-AMCs